Manajemen pengelolaan informasi departemen humas pt pal indonesia (persero) dalam membangun citra baik perusahaan pada isu bumn merugi di era revolusi industri 4.0 - Kusuma, Reri Septiana; Wahyuningsih, Sri (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
Information management carried out by PT PAL Indonesia (Persero) uses Instagram as a social media listening in monitoring issues as well as being used as an analytic social media to the audience to determine tastes and segmentation in order to build good corporate image communication. The purpose of this research is to find out how the management of the information department of the Public Relations department of PT PAL Indonesia (Persero) in building a good image of the company on issues related to BUMN loss in the industrial revolution era 4.0. Data collection methods using observation, interviews, and documentation. The informants were selected using purposive sampling method. Data analysis using Miles and Huberman techniques, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that in the information management carried out by PT PAL Indonesia (Persero) using Instagram as an analytic media as well as in building a good image of the company. PT PAL Indonesia (Persero) set the agenda for each upload to frame the issue of loss-making BUMN that dragged PT PAL Indonesia (Persero) as an effort to form a good image of the company. Keywords: Information Management; Social Media Listening; Agenda Setting; Company Good Image